PREDIKSI PERTUMBUHAN PERBANKAN SYARIAH DI INDONESIA TAHUN 2020 DENGAN QUANTITATIVE METHODS - Aam Slamet Rusydiana (Universitas Siliwangi, 2019)
This study aims to predict the growth of Islamic banks assets in Indonesia for the year 2020. There are three schemes of forecasting count: pessimistic, moderate and optimistic. The results show that with the Multiplicative Decomposition method, the assets of Indonesian Islamic banks are estimated to reach Rp 523.72 trillion at the end of 2020. Slightly different from those results, with the trend analysis method, the assets of Indonesian Islamic banks are estimated at Rp 516.09 trillion. As for using the exponential smoothing approach with a trend at the end of 2020 the assets of Indonesian Islamic banks are estimated to reach Rp. 553 trillion. So, if nothing extraordinary happens - which is inorganic - and the assumption of 'ceteris paribus', the assets of Islamic banks in Indonesia at the end of 2020 will be in the range of Rp. 516 to Rp. 553 trillion 'only'. The growth of Indonesian Islamic banks asset in 2020 is between 7.3%-14.9%. This is expected to be realized.